Pemahaman Mengenai Kewirausahaan Untuk Siswa Yayasan Al-Kamilah - Afrimadona; Sindy Yulia Putri; Jati Satrio; Asep Kamaluddin Nashir (CV. Multi Kreasi Media, 2023)
This activity aims to increase entrepreneurship understanding among students of the Al-Kamilah Foundation. The research was conducted using entrepreneurship training and mentoring methods. The training included an understanding of entrepreneurship concepts, business idea development, marketing, financial management, and product development. The results of the activity showed an improvement in students' entrepreneurship understanding, as seen from the increased interest of students in developing business ideas and improved skills in managing businesses. In addition, the activity also showed a change in students' attitudes towards entrepreneurship, where previously it was considered as an unattractive career option, but after the training, students began to understand and appreciate the importance of entrepreneurship in life. Therefore, entrepreneurship training and mentoring for students can be a solution in improving entrepreneurship understanding among the younger generation, thus helping to increase economic growth in the future.